A Self Assistive Device for Deaf & Blind People Using IOT. - Vasanth K; Macharla, Mounika; Varatharajan R (Journal of Medical Systems, 2019)
This paper presents Google speech API based aid for deaf and blind people. The live streaming speech on the microphone is sent to Google API server which converts the speech signal into text and displaying onto a LCD screen and amplifies the speech via speaker. The aid will use Request procedure protocol to send the encoded Mp3 audio to Google API server where the speech signal is converted into suitable text and sent back to the Raspberry pi using repeated request protocol. This aid is designed to address issue with mild deafness and blind person. This will enable the deaf and blind persons to work effectively at home, office and any public places with ease. The aid works at low latency at good internet connectivity.